Self‐Healing, Water‐Retaining, Antifreeze, Conductive PVA/PAA‐PAM‐IS/GC Composite Hydrogels for Strain and Temperature Sensors. Issue 7 (28th March 2022) - Min, Jinbiao; Zhou, Zhaoxi; Zheng, Jia; Yan, Caibin; Sha, Hongyuan; Hong, Maochun; Fu, Heqing
Abstract: In this paper, PVA/PAA‐PAM‐IS/GC composite hydrogels are prepared using polyvinyl alcohol (PVA), poly acrylic acid (PAA), poly acrylamide (PAM), and iron sulfate hydrate (IS) glycerol (GC). The crosslinking network is formed by the coordination of carboxyl groups with ions, which forms PVA with semi‐interpenetrating network. The mechanical properties and self‐healing properties of PVA/PAA‐PAM‐IS/GC composite hydrogels are excellent. The stress, strain and self‐healing efficiency of PVA/PAA‐PAM‐IS/GC composite hydrogels can reach 840 kPa, 784%, and above 95%, respectively. The antifreeze and water retention properties of PVA/PAA‐PAM‐IS/GC composite hydrogels are improved by glycerol. PVA/PAA‐PAM‐IS/GC composite hydrogels remains flexible at low temperatures and moist for a long time at room temperature. The conductivity of the hydrogel increases with the increase of temperature because the interactions between glycerol, water molecules and ammonium ions are affected by the temperature, the multifunctional conductive hydrogel can be used in strain sensing and temperature sensing. In summary, PVA/PAA‐PAM‐IS/GC composite hydrogels can provide a guide in the field of electronic intelligence. Abstract : The network of PVA/PAA‐PAM‐IS/GC composite hydrogels is formed by the copolymerization of acrylic acid and acrylamide and the coordination crosslinking of iron ion and carboxyl group. A semi‐interpenetrating network is constructed by the entanglement of polyvinyl alcohol and polyacrylate‐acrylamide.